Detection and management of familial hypercholesterolaemia in primary care in Australia: protocol for a pragmatic cluster intervention study with pre-post intervention comparisons. Issue 10 (22nd October 2017) - Arnold-Reed, Diane E; Brett, Tom; Troeung, Lakkhina; Vickery, Alistair; Garton-Smith, Jacquie; Bell, Damon; Pang, Jing; Grace, Tegan; Bulsara, Caroline; Li, Ian; Bulsara, Max; Watts, Gerald F
Abstract : Introduction: Familial hypercholesterolaemia (FH), an autosomal dominant disorder of lipid metabolism, results in accelerated onset of atherosclerosis if left untreated. Lifelong treatment with diet, lifestyle modifications and statins enable a normal lifespan for most patients. Early diagnosis is critical. This protocol trials a primary care-based model of care (MoC) to improve detection and management of FH. Methods and analysis: Pragmatic cluster intervention study with pre-post intervention comparisons in Australian general practices. At study baseline, current FH detection practice is assessed. Medical records over 2 years are electronically scanned using a data extraction tool (TARB-Ex) to identify patients at increased risk. High-risk patients are clinically reviewed to provide definitive, phenotypic diagnosis using Dutch Lipid Clinic Network Criteria. Once an index family member with FH is identified, the primary care team undertake cascade testing of first-degree relatives to identify other patients with FH. Management guidance based on disease complexity is provided to the primary care team. Study follow-up to 12 months with TARB-Ex rerun to identify total number of new FH cases diagnosed over study period (via TARB-Ex, cascade testing and new cases presenting). At study conclusion, patient and clinical staff perceptions of enablers/barriers and suggested improvements to the approach will be examined. Resources at each stage will be traced to determine the economic implications of implementing the MoC and costed from health system perspective. Primary outcomes: increase in number of index cases clinically identified; reduction in low-density lipoprotein cholesterol of treated cases. Secondary outcomes: increase in the number of family cases detected/contacted; cost implications of the MoC. Ethics and dissemination: Study approval by The University of Notre Dame Australia Human Research Ethics Committee Protocol ID: 0 16 067F. Registration: Australian New Zealand Clinical Trials Registry ID: 12616000630415. Information will be disseminated via research seminars, conference presentations, journal articles, media releases and community forums. Trial registration number: Australian New Zealand Clinical Trials Registry ID 12616000630415; Pre-results.